2022
DOI: 10.3390/jcm11020439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Predictors of In-Hospital Mortality among Older Patients with Acute Heart Failure

Abstract: Acute Heart Failure (AHF)-related hospitalizations and mortality are still high in western countries, especially among older patients. This study aimed to describe the clinical characteristics and predictors of in-hospital mortality of older patients hospitalized with AHF. We conducted a retrospective study including all consecutive patients ≥65 years who were admitted for AHF at a single academic medical center between 1 January 2008 and 31 December 2018. The primary outcome was all-cause, in-hospital mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In-hospital mortality rates for acute heart failure range from 4% to 13%, and the mortality rate within one year after discharge is approximately 25% to 30%. Additionally, there is a significant readmission rate, with over 45% of patients requiring readmission following their initial discharge [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital mortality rates for acute heart failure range from 4% to 13%, and the mortality rate within one year after discharge is approximately 25% to 30%. Additionally, there is a significant readmission rate, with over 45% of patients requiring readmission following their initial discharge [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In our country, studies such as Escobar et al focused on hospitalized patients of internal medicine and showed in-hospital mortality at 9.5%; these percentages may significantly increase when a geriatric population is being considered—potentially as high as 11% mortality [ 7 ]. In Spain, hospital mortality during admissions for acute HF is variable and constitutes a major problem from the point of view of public health and cost efficiency, putting a strain on healthcare expenditures [ 1 , 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of young patients deny history of chest pain prior to MI. 1 Approximately one to two percent of the adult population in developed countries has Heart failure, with the prevalence of more than 10 percent among persons age less than or equal to seventy years of age. However, in younger individual it is also prevalent.…”
Section: Introductionmentioning
confidence: 99%